Current Overview of Osteogenesis Imperfecta - Deguchi, Mari; Tsuji, Shunichiro; Katsura, Daisuke; Kasahara, Kyoko; Kimura, Fuminori; Murakami, Takashi (Medicina (Kaunas, Lithuania), 2021)
Osteogenesis imperfecta (OI), or brittle bone disease, is a heterogeneous disorder characterised by bone fragility, multiple fractures, bone deformity, and short stature. OI is a heterogeneous disorder primarily caused by mutations in the genes involved in the production of type 1 collagen. Severe OI is perinatally lethal, while mild OI can sometimes not be recognised until adulthood. Severe or lethal OI can usually be diagnosed using antenatal ultrasound and confirmed by various imaging modalities and genetic testing. The combination of imaging parameters obtained by ultrasound, computed tomography (CT), and magnetic resource imaging (MRI) can not only detect OI accurately but also predict lethality before birth. Moreover, genetic testing, either noninvasive or invasive, can further confirm the diagnosis prenatally. Early and precise diagnoses provide parents with more time to decide on reproductive options. The currently available postnatal treatments for OI are not curative, and individuals with severe OI suffer multiple fractures and bone deformities throughout their lives. In utero mesenchymal stem cell transplantation has been drawing attention as a promising therapy for severe OI, and a clinical trial to assess the safety and efficacy of cell therapy is currently ongoing. In the future, early diagnosis followed by in utero stem cell transplantation should be adopted as a new therapeutic option for severe OI.